Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.ypmed.2011.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of preventive measures during and after the 2009 influenza A (H1N1) virus pandemic peak in Spain

Abstract: In addition to demographic factors, modifiable factors such as personal beliefs and expectations play a role in the adoption of preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 14 publications
11
47
1
1
Order By: Relevance
“…Our study showed that the expected vaccination uptake is largely dependent on the seriousness of a pandemic. This was also shown in previous studies, including studies conducted in the Netherlands, Poland, Spain and Sweden [39][40][41][42][43][44][45]. During the influenza A(H1N1)pdm09 pandemic, the perceived vulnerability was low and respondents believed that they were less likely to become infected than other people [41,46].…”
Section: Results In Relation To Other Studiessupporting
confidence: 71%
“…Our study showed that the expected vaccination uptake is largely dependent on the seriousness of a pandemic. This was also shown in previous studies, including studies conducted in the Netherlands, Poland, Spain and Sweden [39][40][41][42][43][44][45]. During the influenza A(H1N1)pdm09 pandemic, the perceived vulnerability was low and respondents believed that they were less likely to become infected than other people [41,46].…”
Section: Results In Relation To Other Studiessupporting
confidence: 71%
“…The perception of social alarm regarding H1N1 influenza was similar to that in other population‐based studies . However, this perception of social alarm was slightly higher in primary schools, where perceived absenteeism among students was also higher than in schools imparting secondary education only.…”
Section: Discussionsupporting
confidence: 82%
“…As observed in other studies, electronic mail was found to be an appropriate communication channel, as nearly all the schools reported having received the information in this way and it was highly valued. In future potential threats, the use of similar communication strategies would seem a good choice.…”
Section: Implications For School Healthsupporting
confidence: 68%
See 2 more Smart Citations